2004
DOI: 10.1038/sj.onc.1207207
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-independent activation of erbBs signaling and estrogen receptor α in the mouse vagina exposed neonatally to diethylstilbestrol

Abstract: Growth factors and estrogen receptor (ER) signaling cooperate to play essential roles in cell proliferation, differentiation and tumor progression in mouse reproductive organs. Treatment of neonatal mice with diethylstilbestrol (DES) induces an estrogen-independent persistent proliferation and cornification of the vaginal epithelium, which results in cancerous lesions later in life. However, the mechanisms of the estrogen-dependent andindependent pathways essentially remain unknown. We characterized the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 44 publications
3
51
0
Order By: Relevance
“…We have analyzed the factors involved in vaginal cell proliferation and differentiation focusing on growth factors and cytokines (Miyagawa et al 2004). The novel finding in the present study is that genes related to the IL-1 system (IL-1L1 and IL-1 RII) were increased in expression in the neoDES vagina.…”
Section: Microarray Analysis Of Gene Expression Changes In the Neodesmentioning
confidence: 56%
See 1 more Smart Citation
“…We have analyzed the factors involved in vaginal cell proliferation and differentiation focusing on growth factors and cytokines (Miyagawa et al 2004). The novel finding in the present study is that genes related to the IL-1 system (IL-1L1 and IL-1 RII) were increased in expression in the neoDES vagina.…”
Section: Microarray Analysis Of Gene Expression Changes In the Neodesmentioning
confidence: 56%
“…For example, in the vagina, neonatal estrogen administration induces persistent cell proliferation and cornification of vaginal epithelium even after ovariectomy (OVX), resulting in hyperplastic lesions later in life (Takasugi et al 1962, Forsberg 1979, McLachlan et al 1980. We previously reported that persistent erbB receptor phosphorylation and sustained expression of epidermal growth factor-like growth factors contributed to persistent action in the neonatally DES-exposed vagina (Miyagawa et al 2004). However, the underlying mechanisms remain unknown, therefore, additional factors must be present.…”
Section: Introductionmentioning
confidence: 99%
“…ErbB signaling has long been implicated downstream of steroid hormone signaling in female reproductive organs (8,9,33). In the current study, we found that the erbB ligand, AREG, is expressed specifically in the epithelium, dependent on epithelial ESR1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA (2 μg), isolated from each group using an RNeasy kit (Qiagen), was used in RT-PCR reactions carried out with SuperScript III reverse transcriptase and SYBR Green Master Mix (Life Technologies), according to manufacturer's instructions. PCR conditions and sequences of some primer sets are given in a previous report (33). Others used are Pgr, TAT GAG AAC CCT TGA CGG TGT TG, CAG GGC CTG GCT CTC GTT A; Cebpb, CGG GTT TCG GGA CTT GAT GCA AT, CTA GAC AGT TAC ACG TGT GTT GCG.…”
Section: Methodsmentioning
confidence: 99%
“…EGFR-targeted therapy has been validated in human colorectal cancer (14), and the chemotherapeutics include pharmacological agents, including cetuximab (Erbitux), which is an EGFR inhibitor (15). EGFR acts to bind an EGFR-selective ligand activated by epidermal growth factor (EGF), transforming growth factor-α, amphiregulin or neuregulin, finally leading to cell proliferation, invasion and the inhibition of apoptosis (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%